Robust control of flow separation over a pitching aerofoil using plasma actuators. Issue 1 (July 2017) - Pasquale, L.; Broglia, R.; Choi, K.-S.; Durante, D.; Zanchetta, P.
Abstract: We address the problem of controlling the unsteady flow separation over an aerofoil, using plasma actuators. Despite the complexity of the dynamics of interest, we show how the problem of controlling flow separation can be formulated as a simple output regulation problem, so that a simple control strategy may be used. A robust multivariable feedback control is designed and tested in a configuration with two actuator/sensor pairs. Accurate numerical simulations of incompressible flows on a pitching NACA 0012 at Reynolds Re = 20, 000 are performed in order to illustrate the effectiveness of the proposed approach. Robust, fast flow reattachment is achieved, along with both stabilisation and increase/reduction of the lift/drag, respectively. The control system shows good dynamic performances, as the angle of attack is varied. The chosen output can be experimentally measured by appropriate sensors and the extension of the proposed approach to 3D configurations is straightforward.